2021
DOI: 10.1155/2021/9934533
|View full text |Cite
|
Sign up to set email alerts
|

Altered Profile of Fecal Microbiota in Newly Diagnosed Systemic Lupus Erythematosus Egyptian Patients

Abstract: Background. Dysbiosis of gut microbiota could promote autoimmune disorders including systemic lupus erythematosus (SLE). Clarifying this point would be of great importance in understanding the pathogenesis and hence the development of new strategies for SLE treatment. Aim. This study aimed to determine the fecal microbiota profile in newly diagnosed SLE patients compared to healthy subjects and to investigate the correlation of this profile with disease activity. Methods. Newly diagnosed SLE patients who fulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Specifically, decreased phylum Firmicutes along with increased phylum Proteobacteria and Bacteroidetes were observed in the fecal samples of patients with MG. Accordingly, the ratio of Firmicutes/Bacteroidetes (F/B ratio) in patients with MG was markedly lower, which was consistent with the decreased F/B ratio observed in systemic lupus erythematosus and inflammatory bowel disease ( 62 , 63 ). In fact, the F/B ratio can reflect a pro-inflammatory environment, where the inflammatory microbiota could damage the intestinal epithelium and subsequently trigger an immune response, leading to immunological imbalance.…”
Section: Dysbiosis Of Gut Microbiota and Microbial Metabolites In Patients With Mgsupporting
confidence: 74%
“…Specifically, decreased phylum Firmicutes along with increased phylum Proteobacteria and Bacteroidetes were observed in the fecal samples of patients with MG. Accordingly, the ratio of Firmicutes/Bacteroidetes (F/B ratio) in patients with MG was markedly lower, which was consistent with the decreased F/B ratio observed in systemic lupus erythematosus and inflammatory bowel disease ( 62 , 63 ). In fact, the F/B ratio can reflect a pro-inflammatory environment, where the inflammatory microbiota could damage the intestinal epithelium and subsequently trigger an immune response, leading to immunological imbalance.…”
Section: Dysbiosis Of Gut Microbiota and Microbial Metabolites In Patients With Mgsupporting
confidence: 74%
“…OTU 165 ( Bifidobacterium bifidum ), one of the bacteria in the synbiotic used in this study, increased in the synbiotic group from 1.04 to 1.21 ( p = 0.93) and decreased from 0.86 to 0 ( p = 0.38) in the placebo group. OTU 068 ( Ruminococcus gnavus ), which is in a study by Azzouz et al [ 9 ] was found to be highly represented in SLE patients, decreased from 38.96 to 17.65 ( p = 1) in the synbiotic group and increased from 3.97 to 19.56 ( p = 0.51) in the placebo group.…”
Section: Resultsmentioning
confidence: 95%
“…A study in young, female, lupus-prone mice showed depletion of Lactobacilli compared with age-matched healthy controls [ 8 ]. Studies in patients with SLE have reported significant decreases in the species richness, species diversity and Firmicutes/Bacteroidetes ratio compared with healthy controls and also changes in the metabolic function of gut microbiota [ 9 , 10 , 11 , 12 ]. Another study from China found increased Bacteroidetes , Proteobacteria, Actinobacteria and decreased Firmicutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were few randomized controlled trials (RCTs) about the Lactobacillus ’s effect on SLE patients, a large amount of cohort clinical studies on the relation between Lactobacillus and SLE were increasing. Newly diagnosed treatment-naive SLE cases ( 44 ) and SLE patients that had not received glucocorticoid (GC) therapy ( 45 ) possessed a decrease of Lactobacillus in feces in Chinese and Egyptian patients compared with the healthy controls. However, SLE patients in most cohorts both active and remissive, both adults and children all manifested the enrichment of Lactobacillus in both fecal and oral sample in China and Netherlands ( 14 , 15 , 18 , 19 , 46 ) ( Table 1 ).…”
Section: Lactobacillus Are Altered In Sle Patientsmentioning
confidence: 99%